PENGARUH TINGKAT PENDIDIKAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA TANGERANG SELATAN - Haifa Ukhtina; Liawati (Journal of Research and Publication Innovation, 2025)
This study aims to find out whether there is an influence of education level and work motivation on the performance of employees at the South Tangerang City Library and Archives Office, both partially and simultaneously. The method used is quantitative. The object of this study was employees of the South Tangerang City Library and Archives Service which amounted to 70 respondents. The data collection method used was observation and questionnaire. The data analysis used included validity tests, reliability tests, classical instrument tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. Education level (X1) and work motivation (X2) had a significant effect on employee performance (Y) with the regression equation Y = 2.223 + 0.561 (X1) + 0.377 (X2). The value of the correlation coefficient of influence between the free variable and the bound variable was obtained as 0.878, meaning that it can be concluded that it has a strong relationship. The value of the determination coefficient had a simultaneous effect of 0.765 or 76.5% while the remaining 23.5% was influenced by other factors. The hypothesis test obtained a Fcal > Ftable value of 113.189 > 3.13. So it can be concluded that H0 is rejected and H3 is accepted, meaning that there is an influence of education level (X1) and work motivation (X2) on employee performance (Y).